2020
DOI: 10.20944/preprints202008.0218.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging in Hepatocellular Carcinoma as a Predictor of a Response to Cisplatin-Based Hepatic Arterial Infusion Chemotherapy

Abstract: This study aimed to identify the utility of diffusion-weighted magnetic resonance (MR) imaging with an apparent diffusion coefficient (ADC) map as a predictor of the intrahepatic response of hepatocellular carcinoma (HCC) to cisplatin-based hepatic arterial infusion chemotherapy (HAIC). We retrospectively evaluated 113 consecutive patients with HCC who underwent gadoxetic acid-enhanced and diffusion-weighted MR imaging. The appropriate cutoff for the tumor-to-liver ADC ratio was determined to be 0.741. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, several studies have investigated the role of ADC in HCC; for instance, Jing et al [57] found ADC value combined with tumor size can be used as a noninvasive method for preoperative evaluation of HCC. Besides, ADC has also been evaluated as a predictor of response to therapy, such as cisplatin-based hepatic arterial infusion chemotherapy [58] or stereotactic ablative radiotherapy [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have investigated the role of ADC in HCC; for instance, Jing et al [57] found ADC value combined with tumor size can be used as a noninvasive method for preoperative evaluation of HCC. Besides, ADC has also been evaluated as a predictor of response to therapy, such as cisplatin-based hepatic arterial infusion chemotherapy [58] or stereotactic ablative radiotherapy [59].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic arterial infusion chemotherapy (HAIC) is considered a treatment option for BCLC stage B or C, instead of systemic chemotherapy, for reducing intrahepatic tumor burden by administering cytotoxic chemotherapeutic agents with high intrahepatic concentrations [8,9]. In addition, it can also be used in the poor responders of transarterial chemoembolization [10,11].…”
Section: Introductionmentioning
confidence: 99%